Hubungan Depresi, Ansietas, dan Stres dengan Status Gizi pada Mahasiswa Fakultas Kedokteran Universitas Lampung - Sekar Ronna Fiskasari; Dian Isti Angraini; Muhammad Yusran (CV. Jasa Sukses Abadi, 2020)
Nutritional problems that are still faced by adolescents in Indonesia are underweight, overweight, and obesity, which are interpretations of malnutrition. Multiple factors play a role in the formation of nutritional status, including psychological factors that can be seen through depression, anxiety, and stress status. This research aimed to find the relationship between depression, anxiety, and stress with nutritional status in students of Medical Faculty Lampung University. A cross sectional research was performed involving 107 subjects, which calculated by unpaired categorical comparative formula, taken from students of Medical Faculty Lampung University by purposive sampling. Nutritional status, which determined by BMI, was measured by using body weight scale and stature meter, while depression, anxiety, and stress were measured by using Depression, Anxiety, Stress Scale 42 (DASS-42). Data were analyzed by using Chi-Square test. There were 45,5% subjects with poor nutritional status, 21,5% subjects with depression, 43,9% subjects with anxiety, and 26,2% subjects with stress. Bivariate analysis showed that there was no relationship between depression and nutritional status (p=0,321), there was no relationship between anxiety and nutritional status (p=0,100), and there was no relationship between depression and nutritional status (p=0,110). There were no relationship between depression, anxiety, and stress with nutritional status in students of Medical Faculty Lampung University.